AB0833 Real-world efficacy and safety of secukinumab: data from verona's cohort. (12th June 2018) - Martinis, F.; Caimmi, C.; Carletto, A.; Fracassi, E.; Rossini, M.
Abstract : Background: Secukinumab has been approved for the treatment of active ankylosing spondilytis (AS) and psoriatic arthritis (PsA). Its efficacy has been demonstrated in phase III trials where eligibility criteria ensured a homogeneous population. Although this strategy reduces confounding factors, it does not guarantee the same results in the real world, where clinicians deal with advanced disease, comorbidities, adherence and persistence challenges. Objectives: Aim of this study was to assess efficacy and safety of Secukinumab in real-world clinical practice. Methods: Patients received Secukinumab (150 or 300 mg) at weeks 0, 1, 2, 3 and 4 as induction therapy and then every 4 weeks as manteinance therapy. Assessment of disease acrivity was done at months 0, 6 and 12 using DAPSA, ASDAS, BASDAI, BASFI, pain VAS. Results: 61 patients affected by PsA (65% females, 35% males) and 29 affected by AS (70% males, 30% females) were included. 64% of patients reached 12 months follow up. Baseline characteristics of both groups are shown in the tables below. In the PsA cohort, the median DAPSA at baseline was 19.5 (IQR 9.6), at 6 months 9.09 (IQR 6.5, p<0.001), at 12 months 8.53 (IQR 6.9, p<0, 001). Median pain VAS showed a downward trend as well, from 6 at baseline (2 IQR) to 4.5 at 6 months (2 IQR) and 4 at 12 months (IQR 1.4). No differences emerged among PsA patterns. Clinical trials did not assess efficacy of Secukinumab in patients previously treated with biologic agents other than anti-TNF agents, due to exclusion criteria. We performed subgroup analysis to evaluate its efficacy in patients previously treated with Ustekinumab, finding a reduction in median DAPSA from 19.4 (IQR 9.8, p<0.001) at baseline to 8.7 (IQR 8.3, p<0.001) at 1 year. In the AS cohort, the median BASDAI at baseline was 5.5 (IQR 2.2), at 6 months 3.6 (IQR 1.2, p<0.001), at 12 months 3.1 (IQR 1, p<0.001). Median BASFI decreased from 4.8 (IQR 2.7) to 3.8 (IQR 2.4, p<0.001) and 3 (IQR 2.4, p<0.001) at 6 and 12 months respectively. ASDAS recuced from 3.02 (IQR 1.65), to 1.21 (IQR 1.92, p<0.001) at 6 months and to 1.05 (IQR 0.7, p<0.001) at 1 years follow up. Median pain VAS dropped off from 7 at baseline (IQR 2) to 4 (IQR, p<0.001) at 6 months and 3 (IQR, p<0.001) at 12 months. Of note, patients with advanced disease (ankylosis of the spine) reported a decrease in pain and morning stiffness, thus improving their quality of life. 4 patients switched therapy at 6 months due to partial response, 1 patient experienced an expected adverse event (Candida infection). Overall, no serious side effects were observed and none resulted in Secukinimab discontinuation. Conclusions: In this first real-world cohorts of patients with PsA and AS Secukinumab has proven to be effective, regardless of PsA subtype, radiographic progression in AS and previous exposure to biologic therapy. The safety profile was favourable and similar to previous studies. Reference: [1] Baeten D, et al. Secukinumab, an Interleukin-17 A Inhibitor, in Ankylosing Spondylitis . NEJM2015; 373 (26): 2534–48. Disclosure of Interest: None declared